2008
DOI: 10.1080/00207450601046798
|View full text |Cite
|
Sign up to set email alerts
|

A Prefrontal Erp Involved in Decision Making During Visual Duration and Size Discrimination Tasks

Abstract: Recently, a late positive component (LPCt) with prefrontal dominance was identified in a duration discrimination task as a marker of decision-making processes (Paul et al., 2003). In the present study, LPCt amplitudes and latencies were measured in visual and size discrimination tasks for the purpose of determining the selectivity of this phenomenon. LPCt amplitudes were larger and latencies shorter for longer stimulus pairs, at a time of maximal behavioral performances. Wave amplitudes were also larger for sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
6
18
0
Order By: Relevance
“…A similar MVPA analysis performed on the post-interval period showed that EEG activity in this period encoded mainly decision-related information. The time periods of this effect are similar to recent findings that suggest the existence of early potentials related to temporal processing, such as the N1P2 [Kononowicz and van Rijn, 2014] and to several studies that have suggested the existence of a Late Positive Component of timing (LPCt) [Bannier et al, 2019;Gontier et al, 2008;Lindbergh and Kieffaber, 2013;Paul et al, 2003Paul et al, , 2011Wiener and Thompson, 2015]. However, although several authors have claimed to find an LPCt, this component has been identified relative to different temporal markers and with different topographies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar MVPA analysis performed on the post-interval period showed that EEG activity in this period encoded mainly decision-related information. The time periods of this effect are similar to recent findings that suggest the existence of early potentials related to temporal processing, such as the N1P2 [Kononowicz and van Rijn, 2014] and to several studies that have suggested the existence of a Late Positive Component of timing (LPCt) [Bannier et al, 2019;Gontier et al, 2008;Lindbergh and Kieffaber, 2013;Paul et al, 2003Paul et al, , 2011Wiener and Thompson, 2015]. However, although several authors have claimed to find an LPCt, this component has been identified relative to different temporal markers and with different topographies.…”
Section: Discussionsupporting
confidence: 87%
“…For example, in the study from Wiener and Thompson [2015], the LPCt was measured as the positive potential evoked at frontocentral electrodes after the response was made by the participant and had higher amplitudes for shorter intervals. In other studies, such as [Gontier et al, 2008;Paul et al, 2003Paul et al, , 2011, the LPCt was measured at prefrontal electrodes after the interval offset and were higher for longer intervals. Recently, two studies have reported a positive post-offset potential at centroparietal electrodes, both with higher amplitudes for shorter intervals [Bannier et al, 2019;Lindbergh and Kieffaber, 2013].…”
Section: Discussionmentioning
confidence: 83%
“…To address this limitation, some investigations have compared temporal discrimination tasks with discrimination of other attributes, such as color (Coull, Vidal, Nazarian & Macar, 2004;Kulashekhar, Pekkola, Palva & Palva, 2016), size (Gontier, Dantec, Paul, Bernard, Lalonde & Rebai, 2008), space (Coull, Charras, Donadieu, Droit-Volet, & Vidal, 2015) and numerosity (Schlichting, de Jong & van Rijn, 2020)). For example, Coull and colleagues (2004), using functional Magnetic Resonance Imaging, found a higher activation of areas such as the pre-SMA and a network of other cortical and striatal areas when participants paid more attention to the duration than the color of a stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The generator of the CNV in the task of duration discrimination is mostly considered to be the prefrontal cortex (Pouthas, 2003; Macar and Vidal, 2004). Another ERP component, the P300 (Picton, 1992), is also related to selective attention in temporal tasks (Macar and Vidal, 2003; Gontier et al, 2007, 2008, 2009; Le Dantec et al, 2007; Mitsudo et al, 2009). The parietal cortex is one of the critical sources of the P300 in the context of attention and working memory (Picton, 1992; Horn et al, 2003; Linden, 2005), and the relationships between the P300 and the parietal cortex were also discussed in the timing literature (Gontier et al, 2007, 2009; Mitsudo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%